Implementing Lifestyle Management Using Health Promotion Model Approach - Khamida Khamida (Journal of Global Pharma Technology, 2020)
Introduction: There are problem-related to student’s health behavior in Islamic boarding schools, they do not washing their hand before they have their meals, hanging wet clothes in their room, and they do not really care about toilet hygiene. The aim of this research was to know the effect of peer group support to student's lifestyle management using health promotion model approach. Method: The design was quasi-experimental, pre-post-test control group the population were students who stayed in Islamic boarding school in Surabaya and Sidoarjo, and the total sample was 100 students, 50 in control group, 50 in the intervention group, the sample taken by simple random sampling. In the intervention group, they’ve got health education and peer group support while the control only got health education by giving a student lifestyle management module. The independent variable was peer group support and the dependent variable Student's lifestyle management. The data were taken by the questionnaire and were analyzed by the Mann Whitney test. Result: The result showed that after the treatment, students in the intervention group have Mean 23.28 SD 4.83 meanwhile the control group has SD 4.27 and Mean 4.38. Conclusion: It means that peer group support could change lifestyle management based on the health promotion model. The leaders or caretakers of Islamic boarding schools are expected to continue to monitor the behavior of students in implementing the management of the student's lifestyle and activate the boarding school health center.Keywords Student, Lifestyle management, Islamic Boarding School Peer Support Group.